The self-renewal signaling pathways utilized by gastric cancer stem cells - Ying Fu; Hui Li; Xishan Hao (Tumor Biology)
Gastric cancer is a leading cause of cancer-related mortality worldwide. Cancer stem cells are the source of tumor recurrence and metastasis. Self-renewal is a marker of cancer stem cells and also the basis of long-lasting survival and tumor progression. Although the mechanism of gastric cancer stem cell self-renewal is not clear, there are several signaling pathways and environmental factors known to be involved. This mini review describes recent developments in the self-renewal signaling pathway of gastric cancer stem cell research. Advancements made in this field of research will likely support the development of novel therapeutic strategies for gastric cancer.